¿Mejor que no lo creas? La relevancia moral de la mentira para la ética profesional a la luz de la defensa técnica en el proceso penal acusatorio - Concha-Camacho, Wilfredo; Laise, Luciano D. (Pontificia Universidad Católica del Perú, 2025)
This article aims to examine whether the so-called «right to lie» exists within the framework of the accusatory criminal procedures. Some defend this right as a necessary extension of the accused’s basic right not to self-incriminate; others, however, argue that the right to remain silent or not to actively cooperate with the prosecutor’s investigation does not imply the possibility of telling lies. Thus, once the accused decides to speak, they are bound to tell the truth, the whole truth and nothing but the truth. Based on a review of the discussion among some of the most relevant thinkers who have addressed the issue of lying (for example, Kant, Constant and Augustine of Hippo), this paper will defend a conciliatory or eclectic claim on the right to lie. We will argue that the debate often turns blurred because moral and epistemic levels are confused when formulating a concept of lying. At the moral level, the notion of lying refers to statements intended to mislead the interlocutor. At the epistemic level, lying consists of intentionally stating things that do not correspond to the actual truth. Therefore, lying is unacceptable from a definition of the moral norms involved; however, in its epistemic aspect, the acceptability of the accused’s lie relates to the exoneration from having to demonstrate the truth of what is being claimed.

Este artículo se dirige a estudiar el llamado «derecho a la mentira» en el marco del proceso penal acusatorio. Algunos suelen defender tal derecho como un desglose necesario del derecho fundamental del acusado a no autoincriminarse; otros, en cambio, sostienen que el derecho a guardar silencio o a no colaborar activamente con la investigación de la parte acusadora no implica la posibilidad de proferir mentiras. Así, una vez que la persona acusada decide hablar, pues no le quedaría más que decir la verdad, toda la verdad y nada más que la verdad. A partir de una revisión de la obra de algunos de los pensadores más relevantes que han abordado la cuestión (por ejemplo, Agustín de Hipona, Constant, Kant y sus intérpretes contemporáneos), este trabajo defenderá una tesis conciliadora o ecléctica sobre el derecho a la mentira. Sostendremos que la discusión suele empantanarse porque se confunde el plano moral y el epistémico al momento de formular un concepto de mentira. A nivel moral, la noción de mentira se refiere a afirmaciones que pretenden inducir a error al interlocutor. Y, a nivel epistémico, la mentira consiste en afirmar intencionadamente cosas que no se corresponden con la verdad material. Así, la mentira es inaceptable desde una definición de las normas morales involucradas; pero, en su faz epistémica, la aceptabilidad de la mentira del acusado remite a la exoneración de demostrar la veracidad de lo que se afirma.
Don’t You Better Believe It? The Moral Significance of Lying for Professional Ethics in Light of the Technical Defense in Adversarial Criminal Procedure
Keywords: Deception; Adversarial procedure; Self-incrimination; Procedural guarantees; Judicial error; Engaño; Proceso adversarial; Autoincriminación; Garantías procesales; Error judicial; https://purl.org/pe-repo/ocde/ford#5.05.01